Comparative study of internal fixation of diaphyseal fractures of both bones of the forearm in adults between intramedullary nailing and plate osteosynthesis - Biswas, Atin; Sabui, Kanchan Kumar; Basu, Anindya; Mandal, Prasun (Asian Journal of Medical Sciences, 2023)
Background: Diaphyseal forearm fracture is one of the most commonly encountered fractures of the upper extremity. The literatures comparing the outcome of plate fixation and intramedullary nailing in adults are scarce and therefore the consensus on superiority of one over the other is lacking. This study was undertaken to compare the outcome of these operative techniques in adults with diaphyseal fracture of both bone forearm. Aims and Objectives: This study was undertaken to compare the outcome of plate fixation and intramedullary nailing in adults with diaphyseal fracture of both bone forearm. Materials and Methods: Patients of 18–70 years of age, with diaphyseal fractures of both bones of the forearm of <21 days old, were recruited. Patients were randomly allocated to two treatment groups: intramedullary nailing and plate osteosynthesis. Patients were followed up at 4th week, 12th week, and 24th week post-operative period. Functional outcome was measured at the end of 24th week based on the Clinical and Radiological parameters by Anderson et al., Score, Grace-Eversman Score, and Disabilities of the Arm, Shoulder and Hand (DASH) Score. Results: This study comprised of 40 cases (n=40) who completed the follow-up period of 24 weeks. Most of the patients treated with plate (80%) demonstrated excellent outcome as per Anderson et al., score while the outcome was unsatisfactory in 50% of those treated with nails. About 90% of the patients of plate group had excellent result in contrast to 50% in case of nail group following Grace Eversman criteria. Considering DASH score, the former group showed mostly excellent (40%) and good (45%) outcome while the latter exhibited mostly fair (55%) and good (30%) result. Conclusion: It may be stated that plate osteosynthesis is a better option in the treatment of diaphyseal fracture of both bones forearm in adults.